Penerapan Model TPS untuk Meningkatkan Pemahaman Nilai Persatuan pada Pembelajaran Pancasila di Kelas VI - Elvira Qotrun Nada; Ibnu Muthi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Instilling the value of unity from an early age is essential in shaping a young generation with tolerance and the ability to live harmoniously in diversity. However, the teaching of Pancasila in elementary schools is still largely carried out through conventional approaches that inadequately address students’ affective development. Instruction often remains teacher-centered and lacks interaction, making it difficult for students to internalize national values in their daily lives. This study aims to examine the effectiveness of implementing the Think Pair Share (TPS) model in enhancing students’ understanding of the value of unity in sixth-grade Pancasila education. The research employed a qualitative approach using a literature review method. Data were collected from scholarly journals, books, and relevant studies published between 2020 and 2025. The data were analyzed using content analysis techniques to explore the patterns of TPS implementation and its impact on students’ comprehension of unity. The findings reveal that the TPS model fosters a collaborative, inclusive, and participatory learning environment, enabling students to grasp and internalize the value of unity more deeply. The stages of TPS—thinking, pairing, and sharing—provide students with opportunities to express opinions, listen to others' perspectives, and reach shared understanding. In addition to improving academic outcomes, this model also significantly contributes to the development of character and social attitudes. In conclusion, the TPS model is an effective and relevant teaching strategy for instilling Pancasila values, particularly unity, within the context of 21st-century learning and the Merdeka Curriculum, which emphasizes active, contextual, and character-based education.